The role of regular physical activity on the prevention and alleviation of gastroesophageal reflux disease and chronic constipation in patients with sedentary lifestyle - Wilczynski, Rafal; Wrona, Weronika; Dorożalska, Małgorzata; Owsik, Julia; Wdowiak, Wiktoria; Ludwisiak, Hanna; Wiązania, Kamil; Wróbel, Szymon (Quality in Sport, 2026)
Background. Gastroesophageal reflux disease (GERD) and chronic constipation represent two of the most common functional gastrointestinal disorders, with elevated prevalence among sedentary individuals. Prolonged sitting acts as a risk factor by increasing intraabdominal pressure, compromising lower esophageal sphincter integrity, delaying colonic transit, impairing pelvic floor strength and inducing adverse shifts in gut microbiota. Aim. This study aimed to evaluate the impact of physical activity and sedentary behaviour on the development and management of GERD and chronic constipation Material and methods. This narrative review analyzed recent publications, predominantly from 2024–2026, identified through manual searches in PubMed, Embase, and Scopus using keywords related to physical activity, sedentary behaviour, GERD, and chronic constipation. Results. For chronic constipation, physical activity consistently accelerates intestinal transit, boosts colonic motility, promotes beneficial microbiota changes, and decreases risk by 30-34% at higher activity levels. Benefits are most pronounced with moderate aerobic modalities and are potentiated by concurrent dietary improvements. Conclusions. Moderate-intensity physical activity is an effective, safe, and low-cost strategy for preventing and managing GERD and chronic constipation. It improves reflux symptoms and bowel function, while high-intensity exercise may aggravate GERD. Reducing sedentary behavior is essential alongside increasing activity levels. Combined lifestyle interventions, including diet, provide the greatest benefit. A “movement-first” approach should be integrated into routine care. Further randomized controlled trials are required to establish optimal exercise prescriptions and clarify diet–activity interactions.